The impact of plant growth promoting bacteria (PGPB) on the development of phytopathogenic fungi - Grobelak, Anna; Napora, Anna; Kacprzak, Małgorzata (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
The main purpose of this study was to evaluate impact of plant growth promoting bacteria (PGPB) on the development of phytopathogenic fungi and correlate it with a potential effects on the growth of plants under unfavorable conditions, in order to improve the efficiency of a phytoremediation process. The conducted research focused on the antifungal properties of PGPB. In this study, 51 isolates of bacteria were obtained after diversified disinfection time from plants growing on soil after sewage sludge amendment. The results revealed that some isolated bacteria, mainly endophytic ones, inhibited the development of Fusarium oxysporum, F. culmorum and Alternaria alternata.